2020
DOI: 10.1101/2020.05.08.084384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ACE2 coding variants in different populations and their potential impact on SARS-CoV-2 binding affinity

Abstract: The susceptibility of different populations to the SARS-CoV-2 infection is not yet understood. A deeper analysis of the genomes of individuals from different populations might explain their risk for infection. In this study, a combined analysis of ACE2 coding variants in different populations and computational chemistry calculations are conducted in order to probe the potential effects of ACE2 coding variants on SARS-CoV-2/ACE2 binding affinity. Our study reveals novel interaction data on the variants and SARS… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Their results showed that two mutations have different frequencies in these two races, affecting ACE2 binding to spike protein. In another study on ACE2 variants in different ethnicities, Lys26Arg mutation in Ashkenazi Jews reduced ACE2 affinity, in contrast to mutations in other populations, including East Asian (Ile468Val), South Asian (Arg219Cys), African and African American (Lys341Arg), European (Asp206Gly), European and South Asian (Gly211Arg) ( Ali et al, 2020 ). In an independent study, ACE2 genotypes in Africa and Eastern Mediterranean population were considered protective against COVID-19 ( Karahalil and Elkama, 2020 ).…”
Section: The Role Of Ace2 Variants In Sars-cov-2 Infection and Severimentioning
confidence: 98%
“…Their results showed that two mutations have different frequencies in these two races, affecting ACE2 binding to spike protein. In another study on ACE2 variants in different ethnicities, Lys26Arg mutation in Ashkenazi Jews reduced ACE2 affinity, in contrast to mutations in other populations, including East Asian (Ile468Val), South Asian (Arg219Cys), African and African American (Lys341Arg), European (Asp206Gly), European and South Asian (Gly211Arg) ( Ali et al, 2020 ). In an independent study, ACE2 genotypes in Africa and Eastern Mediterranean population were considered protective against COVID-19 ( Karahalil and Elkama, 2020 ).…”
Section: The Role Of Ace2 Variants In Sars-cov-2 Infection and Severimentioning
confidence: 98%
“…In contrast, the virus binds more to missense variants ACE-I468V, R219C, K341R, D206G, and G211R (in increasing order), corresponding to frequencies observed in East Asian, South Asian, African and African American, European, European and South Asian populations, respectively. The latter isoforms exhibit higher electrostatic attraction, dominated by van der Waals forces (Ali et al, 2020 ).…”
Section: Ace2 the Main Sars-cov-2 Host Cell Receptormentioning
confidence: 99%
“…Through these approaches, host-cell selectivity of viral receptors could be narrowed down to the level of cell populations, and subpopulations within a tissue or organ with great precision, with inherent prophylactic and therapeutic implications. Differences in the expression of ACE2 missense mutants in different ethnicities were reported (Ali et al, 2020 ). Such heterogeneity could also be reflected at the tissue and cell levels in a given individual, explaining the variabilities in risk, susceptibility and vulnerability of certain organs to become targets of the disease.…”
Section: Perspectives and Possible Avenues For Drug Repurposing And Dmentioning
confidence: 99%
“…In contrast, the virus binds more to missense variants ACE-I468V, R219C, K341R, D206G, and G211R (in increasing order), corresponding to frequencies observed in East Asian, South Asian, African and African American, European and European and South Asian populations, respectively. The latter isoforms exhibit higher electrostatic attraction, dominated by van der Waals forces (Ali et al 2020).…”
Section: Ace and Ace2 And Their Ying-yang Roles In The Renin-angiotenmentioning
confidence: 99%
“…Through these approaches, host-cell selectivity of viral receptors could be narrowed down to the level of cell populations, and subpopulations within a tissue or organ with great precision, with inherent prophylactic and therapeutic implications. Differences in the expression of ACE2 missense mutants in different ethnicities were reported (Ali et al 2020). Such heterogeneity could also be reflected at the tissue and cell levels in a given individual, explaining the variabilities in risk, susceptibility and vulnerability of certain organs to become targets of the disease.…”
Section: Precise Specification Of Viral Cellular Targets Through Singmentioning
confidence: 99%